1997
DOI: 10.52324/001c.8944
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Trade Area Activity in the Great Basin Area

Abstract: Proper assessment of rural retail sector activity would yield effective and targeted retail extension/outreach programs. Pull factors assess a local retail sector's ability to meet local retail demands and to capture outside trade. If the local retail sector's pull factor vaiue is above the threshold value of one, the local retail sector is capturing local and non-local retail demands. Tobit estimation procedures were used for eight retail sectors to determine factors which influence the capture of local and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several studies have found decreased local retail trade in communities' whose local sales tax rate exceeds that of surrounding communities (Fisher 1980;Love 1992;Mikesell 1970;Snodgrass and Otto 1990;Walsh and Jones 1998). Other studies have explored the factors affecting the relative level of retail activity, measured by pull factors, in rural areas (Ebai and Harris 1997;Gale 1996;Gruidl and Andrianocos 1994;Yanagida et al 1991). Here, the questions are aimed at the closely related questions of local government revenue generation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found decreased local retail trade in communities' whose local sales tax rate exceeds that of surrounding communities (Fisher 1980;Love 1992;Mikesell 1970;Snodgrass and Otto 1990;Walsh and Jones 1998). Other studies have explored the factors affecting the relative level of retail activity, measured by pull factors, in rural areas (Ebai and Harris 1997;Gale 1996;Gruidl and Andrianocos 1994;Yanagida et al 1991). Here, the questions are aimed at the closely related questions of local government revenue generation.…”
Section: Introductionmentioning
confidence: 99%